Monkeypox: another pandemic in the making?. Issue 3 (4th May 2023) - Sohal, Prinay; Gupta, Aakanksha; Gupta, Shefali; Gupta, Vasu; Jain, Ridhimaa; Jain, Rohit
Abstract: Monkeypox is a zoonotic disease caused by the monkeypox virus, which is a member of the Poxviridae family of viruses. It is transmitted through direct or indirect contact with fluid secretions. Initial symptoms include fever, chills, headache, and malaise, followed by a maculopapular rash that starts on the face and progresses centrifugally. Polymerase chain reaction is the preferred laboratory test for the diagnosis, and management is mostly supportive. The clinical presentation of monkeypox is quite similar to that of another member of the Poxviridae family: smallpox, which wreaked havoc in the 20th century, before being eradicated with the help of the vaccinia virus vaccine in 1977. This vaccine protects not only against smallpox but also monkeypox; therefore, when use of this vaccine was discontinued, monkeypox had a new susceptible population to infect and way to proliferate and evolve. Initially the disease spread in Africa, but now the more evolved monkeypox is quickly spreading to other countries. On July 23, 2022, the World Health Organization declared this multicountry outbreak a public health emergency of international concern. Given its mutating ability and high transmissibility, we need to quickly devise measures to control this virus before it turns into a pandemic.